Respuesta :
[tex]\\ \rm\Rrightarrow r=2cos\theta-3sin\theta[/tex]
- a(rcosTheta) +b(r sintheta)=ax+by
[tex]\\ \rm\Rrightarrow \dfrac{2}{r}cos\theta-\dfrac{3}{r} sin\theta=1[/tex]
[tex]\\ \rm\Rrightarrow 2x-3y=1[/tex]
[tex]\\ \rm\Rrightarrow 2x-3y-1=0[/tex]
Answer:
[tex](x-1)^2+(y+1.5y)^2=3.25[/tex]
Step-by-step explanation:
[tex]x=r \cos(\theta)[/tex]
[tex]y=r \sin(\theta)[/tex]
Given polar equation:
[tex]r=2\cos(\theta)-3 \sin(\theta)[/tex]
Multiply both sides by r:
[tex]r^2=2r\cos(\theta)-3r \sin(\theta)[/tex]
Know that [tex]x^2+y^2=r^2[/tex]:
[tex]x^2+y^2=2r\cos(\theta)-3r \sin(\theta)[/tex]
Substitute [tex]x=r \cos(\theta)[/tex] and [tex]y=r \sin(\theta)[/tex] :
[tex]x^2+y^2=2x-3y[/tex]
Therefore,
[tex]x^2-2x+y^2+3y=0[/tex]
Complete the square:
[tex](x-1)^2-1+(y+1.5y)^2-2.25=0[/tex]
[tex](x-1)^2+(y+1.5y)^2=3.25[/tex]